Ciprofloxacin resistance in community- and hospital-acquired Escherichia coli urinary tract infections: a systematic review and meta-analysis of observational studies. Issue 1 (December 2015) - Fasugba, Oyebola; Gardner, Anne; Mitchell, Brett; Mnatzaganian, George
Abstract Background During the last decade the resistance rate of urinaryEscherichia coli (E. coli ) to fluoroquinolones such as ciprofloxacin has increased. Systematic reviews of studies investigating ciprofloxacin resistance in community- and hospital-acquiredE. coli urinary tract infections (UTI) are absent. This study systematically reviewed the literature and where appropriate, meta-analysed studies investigating ciprofloxacin resistance in community- and hospital-acquiredE. coli UTIs. Methods Observational studies published between 2004 and 2014 were identified through Medline, PubMed, Embase, Cochrane, Scopus and Cinahl searches. Overall and sub-group pooled estimates of ciprofloxacin resistance were evaluated using DerSimonian-Laird random-effects models. The I2 statistic was calculated to demonstrate the degree of heterogeneity. Risk of bias among included studies was also investigated. Results Of the identified 1134 papers, 53 were eligible for inclusion, providing 54 studies for analysis with one paper presenting both community and hospital studies. Compared to the community setting, resistance to ciprofloxacin was significantly higher in the hospital setting (pooled resistance 0.38, 95 % CI 0.36-0.41 versus 0.27, 95 % CI 0.24-0.31 in community-acquired UTIs, P < 0.001). Resistance significantly varied by region and country with the highest resistance observed in developing countries. Similarly, a significant rise in resistance over time was seen in studies reporting on community-acquiredE. coli UTI. Conclusions Ciprofloxacin resistance inE. coli UTI is increasing and the use of this antimicrobial agent as empirical therapy for UTI should be reconsidered. Policy restrictions on ciprofloxacin use should be enhanced especially in developing countries without current regulations.